Static Archives Management at the Library and Archives Service of West Kotawaringin Regency, Central Kalimantan Province - Naufal Faqih; Jalaludin Muhamad Akbar (Department Library of Governance Institut of Home Affairs, 2025)
Problem Statement: Static archive management is important because it concerns the management of static archives which is the identity and identity of the region, so the author focuses on the problem of static archive management which is due to the suboptimal management of static archives in the Library and Archives Service of West Kotawaringin Regency. Purpose: The purpose of this study is to find out the management of static archives in the Library and Archives Office of West Kotawaringin Regency. Method: This study uses a descriptive qualitative method. Data collection techniques are carried out through observation, interviews, and documentation. The data that has been collected is processed in three stages, namely data reduction, data presentation, and conclusion drawn. Result: The findings obtained by the researcher are that there are obstacles in static archive management. This is shown by 3 (three) indicators of the 2 (two) dimensions of management theory used that are still not optimal, namely planning indicators in the processing of static archives, planning in the maintenance and maintenance of static archives, and the environment. Conclusion: The management of static archives at the Library and Archives Office of West Kotawaringin Regency has been running well despite limitations in several ways. In order to improve the management of static archives, it is recommended to build archive depots far from densely populated areas, submit additional budgets in the APBD, and carry out fumigation for the maintenance of static archives.Keywords: Static Archives; APBD; Archive Depot; Management